DISFUNGSIONAL KEPEMIMPINAN GEMBALA GEREJA AKIBAT INTERVENSI ORANG KAYA - Tambunan, Alki Firton; Situmorang, Yohanes Natanael (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2025)
This study examines dysfunctional leadership within churches due to the intervention of wealthy congregants. Dysfunctional leadership refers to a situation where leaders fail to effectively fulfill their duties and responsibilities, often driven by greed, pride, envy, and inefficient resource management. While the involvement of wealthy congregants sometimes provides financial support, it often brings negative impacts if their motivations lack genuine faith. This can lead to internal conflicts, resource allocation injustice, and even corruption, transforming the church from a place of spiritual growth into a profit-oriented organization. The study employs a qualitative method based on literature review to analyze the causes, indicators, and impacts of dysfunctional leadership on church organizations. Findings indicate that dysfunctional leadership undermines congregational trust, hinders spiritual growth, and distorts the church’s primary function as a faith-based community. Indicators include authoritarian tendencies, lack of collaboration, inefficient resource usage, and leaders prioritizing personal interests over serving the congregation. To address these issues, church leaders must first undergo profound spiritual growth, understand the motivations of congregants, especially wealthy ones, and manage resources equitably and transparently. Transparency in financial management is also essential to prevent conflicts and uphold the church’s integrity. By focusing on spiritual growth, prudent management, and strict oversight, churches can overcome dysfunctional leadership and fulfill their mission as a genuine place for faith and spiritual development.